QUO VADIS OF INDONESIAN ISLAMIC BANKING: A DELPHI STUDY - Abdillah Ubaidi; Imron Mawardi; Luthfi Rosyidi; Nor Balkish Zakaria (Universitas Airlangga, 2025)
This paper aims to determine what factors make Islamic banks in Indonesia have a low market share and what factors will drive Islamic banking to achieve a sustainable competitive advantage. The Delphi approach is used to gather experts' opinions in the Islamic banking field. There are 15 experts involved in three rounds, all representing the stakeholders of the Islamic banking industry in Indonesia, namely academics, government, regulators, community and practitioners. The Delphi panel consensus of the five categories of Islamic banking stakeholders revealed that what causes the Islamic banking market to be low is the implementation of the market share trap and the low assets of Islamic banks as problems to be solved. As for the Islamic finance hub, Islamic values and stakeholder relations as a component system of Islamic banking can gain a sustainable competitive advantage. This study contributes empirically to increasing the market share of Islamic banks and achieving a sustainable competitive advantage of Islamic banking in a dual-banking system. The study will broaden knowledge and provide insight into the sharia economic ecosystem for policymakers, operators, regulators and practitioners of the Islamic banking sector in Indonesia regarding stakeholder perspectives, which can be part of the solution for development in the banking industry. This contribution is an integral part of the roadmap for developing Indonesian banking.